2022
DOI: 10.3390/ijms23179801
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analyses Revealed the Effects of Poly (I:C) on the Liver and Spleen of Argyrosomus japonicus

Abstract: Poly (I:C) can work as an immunostimulant and a viral vaccine; however, its functional mechanism in aquatic animals needs to be further investigated. In this study, comparative transcriptomic analyses were performed to investigate the effects of poly (I:C) on Argyrosomus japonicus at 12 h and 48 h postinjection. A total of 194 and 294 differentially expressed genes were obtained in the liver and spleen, respectively. At 12 h, poly (I:C) injection could significantly influence the function of the metabolism-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…These results suggest that the combined diet may enhance the activation of the complement system in response to both bacterial and viral challenges. This finding aligns with previous studies that have shown an increased induction of c3 following challenges with poly I:C or bacterial pathogens [99][100][101][102]. Further research is needed in order to investigate the mechanisms underlying the dietary effect on the complement activation cascade.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest that the combined diet may enhance the activation of the complement system in response to both bacterial and viral challenges. This finding aligns with previous studies that have shown an increased induction of c3 following challenges with poly I:C or bacterial pathogens [99][100][101][102]. Further research is needed in order to investigate the mechanisms underlying the dietary effect on the complement activation cascade.…”
Section: Discussionsupporting
confidence: 88%
“…However, O. mykiss decreased gene expression of TLR-8, IgM, and MHC II at 48 h. This response was similar in O. mykiss infected with F. psychrophilum, having the lowest levels of mRNA in cell membrane-associated receptors such as TLRs in spleen. [13], in agree Argyrosomus japonicas presented a downregulation of MHC II at 12 and 48 h postinjection with POLY I:C in spleen [47].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, kidney cells can recognize double-stranded RNA [45], ovarian surface epithelia express TLRs 2-5 [43] and cumulus cells express TLRs2, 4, 8, and 9 [46]. POLY I:C induces an antiviral response (TLR-3) in several fish species, such as S. salar [47], and the head kidney cells and liver cells of common carp (Cyprinus carpio) [48] and killifish (Nothobranchius guentheri) [49]. Pham et al (2017) compared the S. salar heart endothelial cell line (ASHe) and the bulbous arteriosus of the fibroblast cell line (BAASf) for their responses to a viral mimic, POLY I:C, and to four RNA viruses: CSV, IPNV, VHSV Iva, and VHSV IVb [50].…”
Section: Discussionmentioning
confidence: 99%
“…Immune-related genes involved in adaptive immunity in Th1, Th17, and Treg cells in the liver of Carassius auratus gibelio were upregulated in response to Myxobolus wulii infection (Zhao et al, 2021). Moreover, the immune-related genes Forkhead Box O1 (FOXO1) and Serum/ Glucocorticoid Regulated Kinase 1 (SGK1) were upregulated in the Argyrosomus japonicus liver after poly I:C stimulation and affected cell survival and mitosis (Xu et al, 2022). In contrast, genes involved in inflammation of the liver are downregulated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the RNA‐seq data reflected a general process from pathogen recognition to inflammatory cytokine generation and delineated a putative Toll‐like receptor (TLR) signaling pathway in the Oncorhynchus mykiss spleen following Flavobacterium psychrophilum infection (Deng et al, 2022). Similarly, polyinosimic:polycytidylic acid (poly I:C) could regulate fish immunity and the inflammatory response in the Argyrosomus japonicus spleen (Xu et al, 2022). In Scortum barcoo , the spleen plays an important role in resistance to S. agalactiae infection by upregulating IL‐21 and IL‐22 (Gao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%